2022
DOI: 10.1002/adom.202202353
|View full text |Cite
|
Sign up to set email alerts
|

Li0.5Na0.5AlB2O4F2: Fluoroaluminoborate with Aligned 1[BO2] Chain Induced by Unprecedented [AlO3F3]6− Species Features Enhanced Birefringence

Abstract: Birefringent materials have been used extensively owing to their indispensable role in creating and modulating polarized light, while birefringent materials for deep ultraviolet (DUV, λ < 200 nm) applications are still urgently needed. Herein, a strategy to induce the formation of birefringence‐active 1∞[BO2] chains driven by AlOmFn units is proposed for designing DUV birefringent materials, and a new fluoroaluminoborate, Li0.5Na0.5AlB2O4F2, with aligned 1∞[BO2] chains and an unprecedented [AlO3F3]6− motif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…In the previous research, few fluoroaluminoborates with excellent optical properties have been reported, and they have been listed in Table S4 in the Supporting Information. As shown in Figure S1 in the Supporting Information, the similar edge-sharing octahedra can be found in other fluoroaluminoborates SrAlB 3 O 6 F 2 , Al 8 (BO 3 ) 4 (B 2 O 5 )­F 8 , SnAl 2 (BO 3 ) 2 F 2 , and Li 0.5 Na 0.5 AlB 2 O 4 F 2 …”
supporting
confidence: 73%
See 1 more Smart Citation
“…In the previous research, few fluoroaluminoborates with excellent optical properties have been reported, and they have been listed in Table S4 in the Supporting Information. As shown in Figure S1 in the Supporting Information, the similar edge-sharing octahedra can be found in other fluoroaluminoborates SrAlB 3 O 6 F 2 , Al 8 (BO 3 ) 4 (B 2 O 5 )­F 8 , SnAl 2 (BO 3 ) 2 F 2 , and Li 0.5 Na 0.5 AlB 2 O 4 F 2 …”
supporting
confidence: 73%
“…Particularly for fluoroaluminoborates, when the Al atom bonds with O/F atoms, the functionalized [AlO m F n ] ( m + n = 4, 5, 6) units can be formed . The introduction of [AlO m F n ] units can make some advantages: The introduction of Al–O/F polyhedra can partially eliminate dangling bonds from the isolated π-conjugated [BO 3 ] and [B 3 O 6 ] groups to increase the energy gap. The rich coordination of Al–O/F mixed-anion units can provide more structural possibilities and restrain the polymerization of B–O groups, which is beneficial to optimize the alignment of the nonlinear optical (NLO) active units with a coplanar and consistent orientation. The symmetry-breaking [AlO m F n ] units by the substitution of O 2– with larger electronegativity F – contribute to increasing microscopic susceptibility and optical anisotropy. Therein, more and more aluminoborates and fluoroaluminoborates with excellent properties were synthesized, such as K 2 Al 2 B 2 O 7 , Rb 3 Al 3 B 3 O 10 F, BaAlBO 3 F 2 , AAlB 3 O 6 F (A = Rb, Cs), , SrAlB 3 O 6 F 2 , and Li 0.5 Na 0.5 AlB 2 O 4 F 2 . Hence, aluminoborates are good candidates for designing UV optical materials, which drives us to perform further exploration.…”
mentioning
confidence: 99%
“…And as shown in Figure S5, the IR spectrum well verified the existence of [BO 3 ] and [BO 4 ] units in structures, which was consistent with results obtained from single-crystal XRD analysis. According to previous research, the stretching vibration signals of the [BO 3 ] can be observed within the spectral range of 1396–1419 cm –1 . The asymmetric stretching signals of the B–O bond in [BO 3 ] appear between 1234 and 1273 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the structures of materials determine their properties, to explore borate DUV optical materials efficiently, we must design the structures from a microscopic perspective. 29–36 Therein, alkali and alkaline earth metals, benefiting from the absence of d–d and f–f electron transitions, can extend the transparent windows into the DUV region. Owing to the different valence states and coordination environments of alkali metals and alkaline earth metals, it is possible to achieve abundant structural assemblies and beneficial arrangements of anionic units by introducing them simultaneously into the materials.…”
Section: Introductionmentioning
confidence: 99%